Bureaucratic Transformation through Digital Innovation: Practices and Challenges of Public Service Delivery in Sumedang Regency - Lalas Sulastri (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
This study examines how digital public service innovation drives bureaucratic transformation in Sumedang Regency by analysing implementation processes, institutional changes, and key implementation barriers. Previous studies on digital public service innovation in Indonesia have predominantly focused on service effectiveness and technological adoption, while limited attention has been given to bureaucratic transformation as a multidimensional institutional process. This study therefore aims to fill this gap by integrating process evaluation, institutional transformation, and implementation barrier analysis within a single evaluative framework. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving 9 informants consisting of local government officials, digital system operators, and community service users. Data analysis was conducted interactively through data reduction, data display, and thematic conclusion drawing based on three evaluation dimensions. The findings indicate that the digitalisation of public services improves administrative efficiency, strengthens transparency, and reshapes bureaucratic structures and work procedures. The transformation is also reflected in the emergence of new digital governance roles and a shift toward a more performance-oriented and responsive bureaucratic culture. However, the transformation process continues to face several challenges, including limited human resource capacity, incomplete inter-agency system integration, uneven institutional commitment, and varying levels of community digital literacy. The study concludes that digital innovation in Sumedang represents a gradual and multidimensional process of institutional transformation rather than merely technological modernisation. Theoretically, this study contributes to the development of digital governance and bureaucratic reform literature by providing a multidimensional analytical framework for understanding institutional transformation in local government digitalisation.